Teaching Pragmatic Competence in EFL Classrooms: The Impact of Speech Act Instruction on Pre-Service English Teachers - Pangemanan, Yopie Alex Tomi; Lalira, James Edward; Scipio, Jane Elvira; Suoth, Royke Max; Tumuju, Vivi Nansy; Mantau, Mercy (Universitas Hamzanwadi, 2025)
Pragmatic competence—the ability to use language appropriately in social contexts—is essential for effective EFL communication but often underemphasized in teacher education. This study examines the impact of speech act-based instruction on developing pre-service English teachers’ pragmatic competence. Participants included 20 second-year students enrolled in the English Education program at Universitas Kristen Indonesia Tomohon. Over four weeks, they attended two 90-minute instructional sessions per week, integrating explicit instruction, role-plays, discourse analysis, and reflective discussions. Multiple instruments were employed: a 30-item pragmatic competence test (combining situational multiple-choice and open-ended tasks), classroom observations, and post-instruction interviews. Quantitative results revealed statistically significant improvements across all levels of speech acts: locutionary (M = 0.437 to 0.5665, p < .001), illocutionary (M = 0.535 to 0.6105, p < .001), and perlocutionary (M = 0.5295 to 0.5565, p < .001). Qualitative findings highlighted increased pragmatic awareness, communicative confidence, and in-class adaptability. However, participants still faced challenges in transferring theoretical knowledge into spontaneous speech, suggesting the need for extended, contextualized instruction. These findings affirm the value of structured pragmatic instruction in EFL teacher training, equipping future educators to model and foster linguistic accuracy and sociocultural fluency in global communication.